The most gender-equal Olympics? A corpus-assisted keywords analysis of Italian press coverage of male and female athletes in Paris 2024 - Simona Frabotta; Javier Fernández-Cruz (Revista de Lingüística y Lenguas Aplicadas, 2025)
The Paris 2024 Olympic Games were the most gender-equal in athlete participation. This article analyzes Italian media coverage to assess the representation of male and female athletes, focusing on narrative equality and gender biases. Using a corpus of Italian daily journal articles, we conducted a Corpus-Assisted Discourse Analysis. Results show that women’s sports received less  coverage  than  men’s,  are  more  likely  to  be  represented  in  traditionally  “feminine”  sports  like  gymnastics,  while  in  other  sports  they  were  underrepresented.  The  media  emphasized  gender  and  regulatory  issues,  especially  concerning  transgender  athletes. Additionally, female athletes were often depicted through emotional lenses, while male athletes were framed through competitiveness  and  achievement.  Despite  growing  participation  equality,  media  portrayals  of  athletes  remain  influenced  by  traditional gendered narratives, indicating a need for further examination as sports media evolves.